EKONOMI HIJAU DALAM PERSPEKTIF HUKUM EKONOMI ISLAM - Maasah, Zahrotul (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2025)
This study explores the relationship between the green economy and Islamic economics, focusing on sustainability. Within Islamic economics, the concept of khilafah (stewardship) is emphasized as a manifestation of individual and collective responsibility towards the environment. The research employs a qualitative library research method, sourcing data from Islamic legal foundations, namely the Qur'an and Hadith, as well as various other references including scholarly journals, articles, research reports, and relevant documents. Data collection is conducted through a literature review technique, involving the examination of pertinent literature, books, and scientific journals related to the research topic. The findings indicate a congruence between the principles of Islamic economics and the concept of the green economy, which has emerged as a viable solution to global challenges in recent decades. Integrating Islamic economic principles with the green economy in the context of sustainability can be implemented through several initiatives, such as green financing by Sharia-affiliated banks, utilization of waqf for environmental projects, Sharia-compliant investments in the renewable energy sector, allocation of zakat funds for environmental programs, and halal certification for environmentally friendly products.